2009
DOI: 10.1177/0961203309345775
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D insufficiency in a large female SLE cohort

Abstract: The objective of this study was to determine the vitamin D status and its relationship with disease and therapy features and with bone mineral density in women with systemic lupus erythematosus. Non-pregnant systemic lupus erythematosus women with dual-energy X-ray absorptiometry and vitamin D measurements performed between May 1 2005 and August 31 2006 were studied. In each patient, the lowest T-score of the first dual-energy X-ray absorptiometry scan during the study period was used. In postmenopausal women,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
136
3
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(158 citation statements)
references
References 23 publications
15
136
3
4
Order By: Relevance
“…Recently, an association between high serum creatinine and low 1,25(OH) 2 D levels in SLE patients was reported (30).…”
Section: Significance and Innovationsmentioning
confidence: 99%
“…Recently, an association between high serum creatinine and low 1,25(OH) 2 D levels in SLE patients was reported (30).…”
Section: Significance and Innovationsmentioning
confidence: 99%
“…This finding may indicate that vitamin D deficiency in our patients was not due to steroid therapy itself. However, Toloza et al [38] found that cumulative corticosteroid exposure in SLE patients was associated with low vitamin D levels.…”
mentioning
confidence: 99%
“…Some have reported an association between vitamin D status and disease activity with lower vitamin D status contributing to greater disease activity (17)(18)(19)(20)(22)(23)(24)(25) . An association between vitamin D and fatigue has also been reported (16,26) ; however, not all studies have observed a relationship between vitamin D and indices of disease activity in SLE (27)(28)(29)(30) . Therefore, currently there is no clear consensus regarding the role of vitamin D in the progression and/or management of SLE.…”
mentioning
confidence: 99%
“…Research in Saudi populations previously used cut-offs in the range of 25-50 nmol/l to denote sufficient vitamin D status; however, more recently a threshold of 75 nmol/l is considered to represent vitamin D sufficiency (39) . The levels of adequate vitamin D status in these two studies (19,20) (17,18,25,28,33) . Two studies report serum 25(OH)D concentrations in the range of 75-80 nmol/l as deficient vitamin D status (12,26) .…”
Section: Prevalence Of Vitamin D Inadequacy In Systemic Lupus Erythemmentioning
confidence: 99%